Wednesday

January 28, 2015

January 28, 2015

Posted by **haritha** on Friday, June 6, 2014 at 8:46pm.

- maths -
**Reiny**, Friday, June 6, 2014 at 11:19pma+bi = √(1+i)/√(1-i)

= √(1+i)/√(1-i) * √(1-i)/√(1-i)

= √(1 - i^2) / (1-i)

= √(1 - i^2) / (1-i) * (1+i)/(1+i)

= √2(1+i)/2

= √2/2 + √2/2 i

so a = √2/2 and b=√2/2

and a^2 + b^2 = 2/4 + 2/4 = 1

**Answer this Question**

**Related Questions**

maths - prove that : 3^-3 * 6^2 * root 98 divided by 5 ^2 * cube root 1/25 * 15...

maths - prove that : 3^-3 * 6^2 * root 98 / 5^2 * cube root 1/25 * 15^-4/3 *3^1/...

maths - prove that : 3^-3 * 6^2 * root 98 / 5^2 cube root 1/25 *(15)^-4/3 *3^1/...

Algebra - Rationalize each expression by building perfect nth root factors for ...

Math - When Synthetically dividing to find a real root out of all Possible Roots...

Math simplifying mixed radicals - Please help me simplify these following mixed ...

maths - find value of a and b in root 3 _1/root 3+1=a+b root 3 if a and b are ...

Maths - Pls help me to show that (1+root x)^5= 10 root x + 20x root x + 2x^2 ]...

maths - 13-a*root 10 whole root = root 8 + root 5 then a equals to ???

Year 11 maths - My teacher said If x-2(square root xy)=9-4(square root 2) so ...